Ehlers-Danlos Syndrome in a Mangalarga–Campolina Crossbreed Mare - Oliveira-Filho, Jose P. [UNESP]; Badial, Peres R.; Liboreiro, Robson M.; Conceição, Lissandro G.; Winand, Nena J.; Borges, Alexandre S. [UNESP] (Elsevier, 2017)
The Ehlers-Danlos syndrome in horses is a group of genetic connective tissue disorders clinically characterized by skin fragility and hyperextensibility. To date, only two of those conditions (Hereditary Equine Regional Dermal Asthenia and Warmblood Fragile Foal Syndrome [WFFS]) have been characterized based on the causative genetic mutations. This report describes the dermatological and histological findings observed in a 3.5-year-old Mangalarga and Campolina crossbreed mare with recurrent skin wounds. Upon dermatological examination, the mare presented with hyperextensible, fragile, and thin skin areas, and scars distributed mainly along the dorsal regions. Histopathological evaluation of affected skin biopsies revealed collagen fibers abnormalities within the deep dermis. The complete PPIB coding region was amplified, but no mutations were observed. Moreover, the PLOD1 gene mutation responsible for WFFS was not present in this animal. To our knowledge, this is the first report describing a Brazilian non-Quarter horse mare with dermatological and histopathological findings of Ehlers-Danlos syndrome.
Keywords: Ehlers-Danlos syndrome; Horse; PPIB